2008
DOI: 10.1387/ijdb.072550ad
|View full text |Cite
|
Sign up to set email alerts
|

Sperm-activating peptides in the regulation of ion fluxes, signal transduction and motility

Abstract: Echinoderm sperm use cyclic nucleotides (CNs) as essential second messengers to locate and swim towards the egg. Sea urchin sperm constitute a rich source of membrane-bound guanylyl cyclase (mGC), which was first cloned from sea urchin testis by the group of David Garbers. His group also identified speract, the first sperm-activating peptide (SAP) to be isolated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
97
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 96 publications
(123 reference statements)
3
97
0
Order By: Relevance
“…Speract binds to its receptor stimulating cGMP synthesis, and this nucleotide activates a K + -selective cyclic nucleotide dependent channel (tetraKCNG) causing a membrane potential hyperpolarization that has been proposed to increase intracellular pH (pHi) and Ca 2+ concentration ([Ca 2+ ]i) (reviewed in [1]). Speract induces [Ca 2+ ]i oscillations that modulate flagellar beating and sperm swimming [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Speract binds to its receptor stimulating cGMP synthesis, and this nucleotide activates a K + -selective cyclic nucleotide dependent channel (tetraKCNG) causing a membrane potential hyperpolarization that has been proposed to increase intracellular pH (pHi) and Ca 2+ concentration ([Ca 2+ ]i) (reviewed in [1]). Speract induces [Ca 2+ ]i oscillations that modulate flagellar beating and sperm swimming [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that spermatozoa swimming up a positive chemoattractant gradient will experience increasing rates of chemoattractant binding and receptor activation, leading to sustained membrane hyperpolarization due to the opening of KCNG channels. This hyperpolarized state is sustained until spermatozoa enter negative chemoattractant gradients, at which point the membrane depolarizes leading to the opening of CaV channels (Guerrero et al, 2010a;Darszon et al, 2008;Bönigk et al, 2009;Strünker et al, 2006;Guerrero et al, 2010b;Galindo et al, 2007;Cook et al, 1994). We found that NFA does not apparently perturb this putative chemoattractant gradient decoding mechanism, indicating that the molecular targets of NFA are downstream of the components regulating the initial Ca 2+ burst.…”
Section: Discussionmentioning
confidence: 58%
“…sperm membrane potential releases CaV channels from inactivation, and stimulates the activity of HCN channels (Darszon et al, 2008). The opening of HCN channels repolarizes V m , leading to opening of CaV channels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8) SAPs increase sperm motility and mitochondrial respiration, and the molecular mechanisms underlying their activation have been well studied. 6) Here, we treated sea urchin sperm with egg seawater (ESW) containing SAPs as positive control for sperm activation, and evaluated the effects of MAF by comparing them with known effects of ESW. Preparation of ESW was as follows: sea urchin eggs were washed with artificial sea water (ASW, 262 mM NaCl, 9 mM KCl, 10 mM CaCl 2 , 48 mM MgCl 2 , 10 mM Hepes, pH 8.0), suspended in 5 mL of ASW, and incubated for 1 h. The concentration of eggs in the suspension was 8:4 Â 10 5 cells/mL.…”
mentioning
confidence: 99%